2017
DOI: 10.1074/jbc.m117.789644
|View full text |Cite
|
Sign up to set email alerts
|

Spermidine promotes Bacillus subtilis biofilm formation by activating expression of the matrix regulator slrR

Abstract: Ubiquitous polyamine spermidine is not required for normal planktonic growth of Bacillus subtilis but is essential for robust biofilm formation. However, the structural features of spermidine required for B. subtilis biofilm formation are unknown and so are the molecular mechanisms of spermidine-stimulated biofilm development. We report here that in a spermidine-deficient B. subtilis mutant, the structural analogue norspermidine, but not homospermidine, restored biofilm formation. Intracellular biosynthesis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 67 publications
1
33
0
Order By: Relevance
“…These dried samples were used for LC-MS analysis as described previously (Lowe-Power et al, 2018). Alternatively, polyamine derivatization by Accufluor reagent and subsequent analysis by HPLC was performed as described previously (Hobley et al, 2017).…”
Section: Polyamine Extraction and Analysismentioning
confidence: 99%
“…These dried samples were used for LC-MS analysis as described previously (Lowe-Power et al, 2018). Alternatively, polyamine derivatization by Accufluor reagent and subsequent analysis by HPLC was performed as described previously (Hobley et al, 2017).…”
Section: Polyamine Extraction and Analysismentioning
confidence: 99%
“…The spirochaete and agent of Lyme Disease Borrelia burgdorferi does not synthesize polyamines but it is absolutely dependent on the spermidine uptake transporter potABCD for growth (Bontemps-Gallo et al, 2018). Polyamines are also essential for robust biofilm formation in Y. pestis (Patel et al, 2006), Vibrio cholerae (Karatan et al, 2005;Lee et al, 2009) and Bacillus subtilis (Burrell et al, 2010;Hobley et al, 2014;Hobley et al, 2017), whereas endogenous polyamines inhibit biofilm formation in Shewanella oneidensis (Ding et al, 2014), A. tumefaciens and Synechocystis (Kera et al, 2018). It has been known for more than 50 years that many Gram-positive species do not contain spermidine or tetraamine spermine ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Zwick et al (37) demonstrated that AhpC is highly expressed in both stationary-phase planktonic cells and biofilms and that strains lacking ahpC do not form a biofilm. In addition, SpeE is a spermidine synthase, and Hobley et al (38) found that spermidine promotes B. subtilis biofilm formation by activating the expression of the matrix regulator slrR. Overall, it is likely that the lower expression of these proteins affects the biofilm development of the sfp mutant.…”
Section: Discussionmentioning
confidence: 99%